2001
DOI: 10.1207/s15328023top2803_09
|View full text |Cite
|
Sign up to set email alerts
|

A Discourse Analysis of Online Classroom Chats: Predictors of Cyber-Student Performance

Abstract: We applied a discourse analysis (DA) to the electronic chat room discussions of a 16-week, Internet-based section of a class in statistical methods in psychology. This analysis revealed that across the semester, several DA categories (e.g., total number of student comments) were correlated with final grade in the class. An additional analysis involving only the chat room discussion of Week 3 revealed that 2 DA categories (i.e., student response to a problem or example given in lecture and total number of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…Our findings confirm that learning analytics can provide pedagogically valuable information, supporting the understanding from earlier studies , Morris et al, 2005, Wang and Tucker, 2001) that data extracted from LMS's can provide pedagogically valuable information of interaction activity throughout a teaching unit. Contemporary educational theorist emphasize the importance of socially orientated pedagogical practices (Austin, 1993, Light, 2001, Tinto, 1997.…”
Section: Final Mark Delivery Methods and Online Participationsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings confirm that learning analytics can provide pedagogically valuable information, supporting the understanding from earlier studies , Morris et al, 2005, Wang and Tucker, 2001) that data extracted from LMS's can provide pedagogically valuable information of interaction activity throughout a teaching unit. Contemporary educational theorist emphasize the importance of socially orientated pedagogical practices (Austin, 1993, Light, 2001, Tinto, 1997.…”
Section: Final Mark Delivery Methods and Online Participationsupporting
confidence: 88%
“…Online discussion forums are designed to build and maintain students' academic relationships with peers and teachers, and while studies (Morris et al, 2005, Davies and Graff, 2005, Wang and Tucker, 2001, Palmer et al, 2008, Dawson, 2010 have looked at discussion forum activity and its impact on marks, there has not been research to identify whether this relationship holds across online and blended modes of delivery and the significance of the comparison between the two. To date there has been minimal research on the relationships between participating in online discussion forums at university and the role participation plays in both online and blended modes of delivery to increase access to social capital.…”
Section: Social Network Theory and Social Capitalmentioning
confidence: 99%
“…In other words, if students are enacting an IRE pattern and is convinced that their instructor is also, they will respond using a narrow number of possible moves Wang, Newlin, and Tucker [38] report a strong correlation between several discourse types and class performance as indicated by final grades. The study supports the notion that "the form and frequency of cyber-students' communicative activity provides critical information regarding their involvement and performance in Internet-based classes" (p. 226).…”
mentioning
confidence: 99%
“…For those who have never taken an online course or who have little computer experience, an online course may be frightening. For example, Wang, Newlin, and Tucker (2001) found that many web based students expressed feelings of intense anxiety about the technology. There are also disadvantages in online courses for individuals who need a great deal of structure.…”
Section: Literature Reviewmentioning
confidence: 99%